Preclinical safety evaluation of WJMSCs and their secretome - Premasangery Kathivaloo; Subramani Parasuraman; Badrul Akmal Hisham Md Yusoff; Raziana Rasib; Karthik Chandran; Kathiresanv.Sathasivam (Penerbit Universiti Kebangsaan Malaysia, 2025)
Mesenchymal stem cells (MSC) are a promising therapy in regenerative medicine due to their unique ability to differentiate into other cells. Among established sources of MSC, MSC derived from Wharton’s jelly (WJSC) of an umbilical cord is a popular source since it involves a painless procedure to obtain the cord with an exceptional proliferation rate compared to other sources. However, the safety and efficacy of MSC must be confirmed through preclinical studies before clinical trials in humans. A study was designed to achieve the maximum tolerable dose (MTD) and safety and toxicity effects of WJSC and its secretomes in animal models. The MTD was achieved through acute toxicity testing on healthy female Sprague Dawley (SD) rats while the safety was assessed using a subchronic toxicity study on healthy male and female SD rats divided into four groups (control, low dose, medium dose and high dose). The safety assessments were then evaluated through biochemical, haematological, and histopathological analyses where the data obtained were analysed using a one-way ANOVA followed by Tukey’s test. Statistical analysis confirmed no significant differences in all tests performed in the study groups. At the study’s termination, neither cells nor secretomes injected rats were found to be deceased and no toxic or severe adverse effects were discovered. Thus, both WJSC and their secretomes applications in humans could be considered harmless for medical purposes.